Treatment for occult hepatocellular carcinoma: does it offer survival advantages over symptom-driven treatment?. (3rd June 2018) - Kim, Kwang Min; Kim, Jiyu; Sinn, Dong Hyun; Kim, Hye Seung; Kim, Kyunga; Kang, Wonseok; Gwak, Geum-Youn; Paik, Yong-Han; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon
Abstract: Objective: In order to claim a benefit of screen-based diagnosis for asymptomatic individuals, treatment of occult disease needs to offer survival advantages compared to the treatment of symptomatic disease, yet information on this issue is scarce with regard to hepatocellular carcinoma (HCC) screening. Methods: A total of 3353 treatment-naïve, consecutive, newly diagnosed HCC patients [age: 57.9 ± 10.3, male: 2, 689 (80.2%), hepatitis B virus: 2555 (76.2%)], diagnosed between 2010 and 2013 were analyzed. Data on the mode of detection was prospectively collected at the time of HCC diagnosis and was used to group patients into occult or symptomatic cases. Results: Overall, 643 (19.2%) patients were symptomatic cases. The proportion of patients undergoing resection, radiofrequency ablation or transplantation were lower in symptomatic cases than occult cases (20.8 vs. 56.2%, p  < .001). Survival was better in occult cases than symptomatic cases (71.2 vs. 30.4% at three-years, p  < .001), with a multivariable-adjusted hazard ratio of 1.40 (95% confidence interval (CI), 1.24–1.58). When stratified by tumor stage, a survival benefit was not observed for patients diagnosed at modified International Union Against Cancer (mUICC) stage I, but presenting symptoms were diverse and nonspecific. In a statistical model adjusting for potential lead-time bias, the association between overall survival and the mode of detection was markedly attenuated and was no longer significant when the treatment modality was included in the model (hazard ratio, 0.94; 95% CI, 0.82–1.07). Conclusion: Treatment of occult disease offered a survival benefit to patients over symptomatic cases. These data support screening practices for asymptomatic individuals to diagnose occult HCC.